Behind the scenes of host-microbe interactions - Prokšová, Magdaléna; Stulík, Jiří; Kubelková, Klára (Vojenské zdravotnické listy, 2020)
Interaction between a host cell and pathogen is a permanent event and can have either adverse outcome leading to disease or great benefit for their mutual co-existence. Understanding pathological host-pathogen interaction is a prerequisite for unveiling the strategies of pathogens virulence. A number of methods exist today for deciphering and characterizing host-pathogen interaction. To increase their sensitivity and accuracy, these methods are commonly used in combinations, such as affinity purification and liquid chromatography-mass spectrometry analysis, cross-linking together with liquid chromatography-mass spectrometry analysis, or stable isotope labeling with amino acids in cell culture with affinity purification. In this review, we focus on study of the early interaction time interval when the pathogen binds and invades the host cell and activates sophisticated mechanisms to overcome the host defense barrier. We briefly describe the methods applied in identifying bacterial-host cell protein interactions while emphasizing these methods' various strengths and weaknesses.
Keywords: interakce hostitele a patogenu; lidé; Disease Transmission, Infectious; Host-Pathogen Interactions; Protein Binding; Humans; vazba proteinů; přenos infekční nemoci